2023
DOI: 10.3390/molecules29010008
|View full text |Cite
|
Sign up to set email alerts
|

New Synthetic Isoxazole Derivatives Acting as Potent Inducers of Fetal Hemoglobin in Erythroid Precursor Cells Isolated from β-Thalassemic Patients

Cristina Zuccato,
Lucia Carmela Cosenza,
Chiara Tupini
et al.

Abstract: Induction of fetal hemoglobin (HbF) is highly beneficial for patients carrying β-thalassemia, and novel HbF inducers are highly needed. Here, we describe a new class of promising HbF inducers characterized by an isoxazole chemical skeleton and obtained through modification of two natural molecules, geldanamycin and radicicol. After preliminary biological assays based on benzidine staining and RT-qPCR conducted on human erythroleukemic K562 cells, we employed erythroid precursors cells (ErPCs) isolated from β-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…HPLC of erythroid cells from a β 0 39/β + -IVSI-110 patient. Modified from Cosenza et al [20] (panel A) and Zuccato et al [18] (panel B) with permission (copyright can be found at https://www.mdpi.com/2073-4425/13/10/1727 and https://www.mdpi.com/1420-3049/29/1/8, respectively; accessed on 25 March 2024) [18,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HPLC of erythroid cells from a β 0 39/β + -IVSI-110 patient. Modified from Cosenza et al [20] (panel A) and Zuccato et al [18] (panel B) with permission (copyright can be found at https://www.mdpi.com/2073-4425/13/10/1727 and https://www.mdpi.com/1420-3049/29/1/8, respectively; accessed on 25 March 2024) [18,20].…”
Section: Introductionmentioning
confidence: 99%
“…From the analytical point of view, these alterations are easily appreciable using HPLC [ 17 , 18 , 19 , 20 ]. In this case, particularly informative is the comparison of chromatograms using lysates from erythroid cells derived from β 0 -thalassemia patients (who produce only trace amounts of HbA) and β + -thalassemia patients (who produce low but clearly detectable amounts of HbA).…”
Section: Introductionmentioning
confidence: 99%